Differentiated Instruction in Secondary Education: A Systematic Review of Research Evidence - Smale-Jacobse, Annemieke E.; Meijer, Anna; Helms-Lorenz, Michelle; Maulana, Ridwan (Frontiers in Psychology, 2019)
This paper provides an overview of theoretical conceptualizations of differentiated instruction and prior findings on its effects for student achievement. Furthermore, by means of a systematic review of the literature from 2006-2016, empirical evidence on the effects of within-class differentiated instruction on secondary school students’ academic achievement is evaluated. Although differentiated instruction has currently gained a lot attention in education, only eleven empirical studies on the topic were selected for review. A narrative description of the selected papers shows that differentiated instruction has been operationalized in many different ways. The selection includes studies on generic teacher trainings for differentiated instruction, ability grouping and tiering, individualization, mastery learning, heterogeneous grouping and remediation in flipped classroom lessons. The majority of the studies show small to moderate positive effects of differentiated instruction on student achievement which gives some indication of the possible benefits of differentiated instruction. However, more research is needed before drawing convincing conclusions regarding the effectiveness and value of different approaches to differentiated instruction for secondary school classes.